2019
DOI: 10.18502/kls.v4i10.3794
|View full text |Cite
|
Sign up to set email alerts
|

The Description of Husband’s Knowledge and Support of Giving Exclusive Breastfeeding in Mekargalih, Jatinangor, Indonesia

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Results of the research in Dhaka Cyti The study showed that no significant association was found between total knowledge score of breastfeeding with remaining sociodemographic variables like age, marital status, family income and expenditure (Afrose et al, 2012) Many factors influence the exclusive breastfeeding, namely mother's knowledge, husband's knowledge, education, attitude, family or husband's support, socio-economic factors, mother's demographics (Afrose et al, 2012;Mohamad et al, 2015;Thet et al, 2016;Alamirew et al, 2017;Elyas et al, 2017;Ratnasari et al, 2017;Senghore et al, 2018;Amelinda, Astuti and Yuliani, 2019;Nurfa'izah, Sinaga and Mabe, 2019;Tsegaye et al, 2019)…”
Section: Level Of Husband's Knowledgementioning
confidence: 98%
“…Results of the research in Dhaka Cyti The study showed that no significant association was found between total knowledge score of breastfeeding with remaining sociodemographic variables like age, marital status, family income and expenditure (Afrose et al, 2012) Many factors influence the exclusive breastfeeding, namely mother's knowledge, husband's knowledge, education, attitude, family or husband's support, socio-economic factors, mother's demographics (Afrose et al, 2012;Mohamad et al, 2015;Thet et al, 2016;Alamirew et al, 2017;Elyas et al, 2017;Ratnasari et al, 2017;Senghore et al, 2018;Amelinda, Astuti and Yuliani, 2019;Nurfa'izah, Sinaga and Mabe, 2019;Tsegaye et al, 2019)…”
Section: Level Of Husband's Knowledgementioning
confidence: 98%